2020
DOI: 10.1186/s12872-020-01733-5
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of early ultrafiltration in patients with acute decompensated heart failure with volume overload: a prospective, randomized, controlled clinical trial

Abstract: Background Ultrafiltration decreases total body water and improves the alveolar to arterial oxygen gradient. The aims of the study were to investigate the efficacy and safety of early ultrafiltration in acute decompensated heart failure (ADHF) patients. Methods 100 patients with ADHF within 24 h of admission were randomly assigned into early ultrafiltration (n = 40) or torasemide plus tolvaptan (n = 60) groups. The primary outcomes were weight loss and an increase in urine output on days 4 and 8 of treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(50 citation statements)
references
References 50 publications
(59 reference statements)
1
47
0
2
Order By: Relevance
“…The readmission event per month is presented in Table 5. The pooled odds of readmission from nine studies (Figure 2) [11][12][13][14][15][16][17][18][19] in 5362 patients was 0.64 (95% CI 0.44, 0.92, P = 0.02) with moderate heterogeneity (I 2 = 46.5). Three studies 13,14,16 reported the HR, one study reported the incidence rate ratio 21 for readmission, and all studies were adjusted for intervention (Supporting Information, Table S8).…”
Section: Readmissionmentioning
confidence: 99%
See 2 more Smart Citations
“…The readmission event per month is presented in Table 5. The pooled odds of readmission from nine studies (Figure 2) [11][12][13][14][15][16][17][18][19] in 5362 patients was 0.64 (95% CI 0.44, 0.92, P = 0.02) with moderate heterogeneity (I 2 = 46.5). Three studies 13,14,16 reported the HR, one study reported the incidence rate ratio 21 for readmission, and all studies were adjusted for intervention (Supporting Information, Table S8).…”
Section: Readmissionmentioning
confidence: 99%
“…The effects of intervention were slightly greater in older patients and in those with longer follow-up periods, but the differences observed between the groups were not statistically significant (P = 0.75 and 0.42, respectively; Figure 3). The effect of intervention was greater (P = 0.001) in patients who received AFMP before discharge 15,20,21 (OR = 0.43) compared with that in those who received AFMP during postdischarge follow-up [11][12][13][14][16][17][18][19]22 (OR = 0.78; Figure 3). The intervention seemed to provide benefit in both types of HF patients (reduced and preserved LVEF), but it was statistically significant only in patients with preserved LVEF ≥ 40% (OR = 0.65, P = 0.02, I 2 = 70%; Figure 4).…”
Section: Readmissionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wenn bei Patienten mit akuter Herzinsuffizienz trotz maximaler diuretischer Therapie keine suffiziente Diurese zu etablieren ist, ist meist der Beginn einer Ultrafiltration notwendig. Entsprechend einer chinesischen Studie mit 100 akut kardial dekompensierten Patienten, kommt dabei der frühzeitigen Nierenersatztherapie eine wesentliche Bedeutung zu [ 12 ]. Im randomisierten Vergleich war die frühe Ultrafiltrationsbehandlung innerhalb von 24 h nach Aufnahme gegenüber einer diuretischen Therapie mit Torasemid und Tolvaptan mit einer stärkeren Abnahme des BNP-Wertes und der NYHA-Klasse assoziiert.…”
Section: Akute Herzinsuffizienzunclassified
“…Im randomisierten Vergleich war die frühe Ultrafiltrationsbehandlung innerhalb von 24 h nach Aufnahme gegenüber einer diuretischen Therapie mit Torasemid und Tolvaptan mit einer stärkeren Abnahme des BNP-Wertes und der NYHA-Klasse assoziiert. Es konnten jedoch keine Unterschiede hinsichtlich der Hospitalisierungs- und Mortalitätsraten nach 1 und 3 Monaten nachgewiesen werden [ 12 ].…”
Section: Akute Herzinsuffizienzunclassified